Comparative multimodal sensory testing in multifocal motor neuropathy and multifocal variant of chronic inflammatory demyelinating polyradiculoneuropathy - T. A. Tumilovich; D. A. Grishina; N. A. Suponeva; P. A. Fedin (Нервно-мышечные болезни, 2024)
Background. One of the key distinctions between multifocal motor neuropathy (MMN) and multifocal variant of chronic inflammatory demyelinating polyradiculoneuropathy (mCIDP) lies in the presence or absence of sensory deficits. Nevertheless, existing literature suggests that MMN can also involve sensory fibers of peripheral nerves, complicating the differential diagnosis of MMN and mCIDP, which remains a relevant issue.Aim. To evaluate the profile and intensity of objective sensory deficits and autonomic dysfunction in MMN and mCIDP, as well as to identify differential diagnostic markers.Materials and methods. Out of 65 patients followed up in the study, 30 were diagnosed with MMN and 35 were diagnosed with mCIDP. A retrospective analysis of clinical and epidemiological characteristics was carried out. The evaluation encompassed clinical assessments of sensory symptoms (including on the NTSS-9 scale), assessments of the severity of autonomic dysfunction using the COMPASS-31 questionnaire, and neurophysiological multimodal sensory testing (including electroneuromyography, computer pallesthesiometry, and short-latency auditory evoked potentials).Results. Patients with mCIDP were significantly more likely to have subjective (according to the NTSS-9 and COMPASS-31 scales) and objective (according to clinical examination) sensory deficits and autonomic dysfunction (p <0.05). A third of patients with MMN reported sensory complaints, yet there was no objective evidence of impaired pain sensitivity. Changes in vibration sensitivity were equally prevalent during clinical assessment in both groups (p >0.05). Electroneuromyography studies revealed significantly lower amplitudes of hand sensory nerve action potentials in the mCIDP group compared to MMN patients (p <0.05). At the same time, a third of patients with MMN with a previous history of disease of 13 [10.0; 16.0] years also had low amplitudes of hand sensory nerve action potentials. The mean value of the autonomic reaction threshold, as well as the cutaneous vibration perception threshold were significantly higher in mCIDP compared to MMN (p <0.05) when examining the hands.Conclusion. Differential diagnosis of MMN and mCIDP at the onset and in early disease (under 5 years) poses no challenges. However, it has been shown that a third of patients with MMN in the long-term catamnesis of the disease have some kind of sensory impairment, which may complicate the differential diagnosis with mCIDP. In such cases, employing computer pallesthesiography to measure vibration perception threshold can aid in clarifying the diagnosis and determining optimal treatment strategies.